Namûdzaj al-Washîlah al-Ta’lîmîyyah li al-Lughah al-‘Arabiyyah fî Mâdah al-Dhâmâir al-Qâimah ‘Alâ Scratch - Bahtiar, Ihwan Rahman; Murodi, Ahmad; Tahir, Akmaludin; Nafi'ah, Khotimatun; Mutmainah, Mia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to develop a Scratch-based learning media product for pronouns material in Arabic language learning at SMA As-Syafi'iyah 02. The method used in this research is the Research and Development with the ADDIE Model (Analyze, Design, Development, Implement, and Evaluate). The five steps taken are: (1) Analyzing, (2) Designing, (3) Developing, (4) Implementing, and (5) Evaluating. The Scratch-based learning media was developed along with media testing by material and media experts. Based on the material expert questionnaire results, a score of 96% was obtained for the category